2021
DOI: 10.1186/s13031-020-00334-5
|View full text |Cite
|
Sign up to set email alerts
|

In the era of humanitarian crisis, young women continue to die in childbirth in Mali

Abstract: Maternal mortality occurs mostly in contexts of poverty and health system collapse. Mali has a very high maternal mortality rate and this extremely high mortality rate is due in part to longstanding constraints in maternal health services. The central region has been particularly affected by the humanitarian crisis in recent years, and maternal health has been aggravated by the conflict. Sominé Dolo Hospital is located in Mopti, central region. In the last decade, a high number of pregnant or delivering women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…4 14 More than 80% of these women's deaths in Mali are preventable. 15 This high maternal mortality ratio, however, comes at the backdrop of various interventions implemented by the government to ameliorate the status quo. [16][17][18][19] For instance, in efforts to improve access to maternal healthcare service, Mali, on 1 January 2005, introduced a fee exemption policy for C-sections which covered the cost of all C-sections including the surgical procedure and preoperative assessments, the surgical kit and postoperative treatment, and hospitalisation in public and private health facilities.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…4 14 More than 80% of these women's deaths in Mali are preventable. 15 This high maternal mortality ratio, however, comes at the backdrop of various interventions implemented by the government to ameliorate the status quo. [16][17][18][19] For instance, in efforts to improve access to maternal healthcare service, Mali, on 1 January 2005, introduced a fee exemption policy for C-sections which covered the cost of all C-sections including the surgical procedure and preoperative assessments, the surgical kit and postoperative treatment, and hospitalisation in public and private health facilities.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Mali’s maternal mortality ratio is estimated to be as high as 562 deaths per 100 000 live births 4 14. More than 80% of these women’s deaths in Mali are preventable 15. This high maternal mortality ratio, however, comes at the backdrop of various interventions implemented by the government to ameliorate the status quo 16–19.…”
Section: Introductionmentioning
confidence: 99%
“…Achieving the global target of less than 70 maternal deaths per 100 000 live births by 2030 requires a mortality reduction more than double the rate achieved between 2000 and 2015. As an immediate measure there is a crucial need to improve quality and coverage of comprehensive SRH services, particularly comprehensive emergency obstetric care, which includes management of PPH; these services should be inclusive of refugee hosting areas 26,27 . Sustained progress in reducing maternal deaths will require progress on health system and multisector enablers and an equity‐driven approach encompassing, inter alia, universal health coverage, poverty reduction, improved nutrition, and gender equality 19…”
Section: Discussionmentioning
confidence: 99%
“…Refugees are especially at great risk of infection and mortality during the pandemic ( Kluge, Jakab, Bartovic, d’Anna, & Severoni, 2020 ) because they mostly live in low- and middle-income countries with limited social and economic resources ( United Nations High Commissioner for Refugees, 2020a ). In such countries, COVID-19 puts an extra burden on already insufficient health care and economic infrastructure ( Fouad, McCall, Ayoub, Abu-Raddad, & Mumtaz, 2021 ; Lancet, 2020 ). Further, refugees are exposed to potentially traumatic events such as torture, injury, and captivation before arriving to host countries ( Steel et al, 2009 ), all of which might affect person’s physical and mental health leaving the person more vulnerable to disease.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, a qualitative study with refugees in Uganda showed that COVID-19 brought significant changes in social and work life. It was also associated with fear, panic, and feeling of helplessness ( Logie et al, 2021 ). In a longitudinal study with Yazidi refugees in Iraq, Kizilhan and Noll-Hussong (2020) showed that the prevalence of post-traumatic stress disorder (PTSD), depressive and anxiety disorders significantly increased during the COVID-19 compared to before the COVID-19 period.…”
Section: Introductionmentioning
confidence: 99%